Bacterial Plasmids Profile from Escherichia coli Resistant to Metronidazole and Nalidixic Acid - Iswara, Arya; Dewi, Sri Sinto (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2016)
bacteria that cause an illness. Antibiotic treatments to a patient have a purpose to eliminate the pathogen bacteria. Bacteria resistance to antibiotic was influenced by the intensity of antibiotic treatment in a region, the uncontrolled antibiotics treatments would increase the antibiotic resistance of bacteria. Plasmids was an extrachromosomal DNA that encodes a functional protein that would eliminate the antibiotic activity. Plasmid is the determinant of bacteria sensitivity to antibiotics. In this case it would be important to find out the bacterial plasmid profile on the E.coli resistant to metronidazole and nalidixic acid antibiotics. This research was using four different sample from faces of diarrhea, ice block, waters from well, and ketchup to cultivate the E. coli. lasmid isolation method was carried out by lyses alkali method. Plasmid profile of the E. coli that resistant to metronidazole and nalidixic acid antibiotics and analyzed using electrophoresis on 1% agarose. E. coli plasmid DNA profile was observed as a fluorescent DNA band in ultraviolet rays. In result, isolated plasmids from bacteria that resistant to antibiotics metronidazole and nalidixic acid having similar size approximately 500 bp, different from bacteria that sensitive to antibiotics metronidazole and nalidixic acid has a smaller size in region of 100 bp.